Parenting: Guiding the Modern Child - Nuryanto, Iis Lathifah; Setiawan, Muhammad Yusuf; Mulyani, Prastiwi Anjar; Sutrisno, Imam Wahyu Pratama; Purwanti, Efin Putri; Rahman, Fauzi; Fidikrila, Sela Latania; Kurniadi, Hafiska; Wahyudi, Deni Qizky; Rusdi, Rona Herjulia (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2026)
The rapid development of the times, especially in the digital era, demands that parents be able to adapt their parenting styles to educate children effectively. This community service activity aims to enhance parents’ understanding and skills in applying parenting approaches that are relevant to the needs of today’s children. The activity was conducted through an interactive lecture and QA discussion, attended by 24 parents representing each neighborhood (RT) in Sorogenen Hamlet, Bantul-DIY. The materials covered included the basic concepts of child and adolescent development, effective parenting styles, and digital parenting strategies such as gadget supervision and open family communication. Evaluation results showed increased participant understanding regarding the importance of authoritative parenting and the active role of parents in guiding children through the challenges of the digital era. This activity demonstrated that community-based parenting education is effective in shaping adaptive, reflective, and proactive parents in raising children. It is hoped that similar programs can be conducted sustainably to build a supportive and responsive family environment for child development.